"Under the radar": exploring "invisible" graduate attributes in tertiary dance education. (18th January 2019) - Longley, Alys; Kensington-Miller, Barbara
Abstract : Purpose: Many graduate attributes (such as adaptability, resilience, cultural awareness and professionalism) are often considered aspirational or invisible and conventionally go "under the radar" of standard university dance education. The purpose of this paper is to add to existing theories of dance as an academic discipline and contributes to studies identifying and mapping graduate attributes across the academy. Design/methodology/approach: The research project Making the Invisible Visible contextualises this paper. It has involved a two-year, cyclical data-gathering process, involving interviews with leading dance employers and academics, and surveys of students from diverse disciplines entering and completing full-time dance degrees. Findings: Due to the centrality of embodiment in studio learning, dance is an unusual discipline within research on graduate attributes and holds a unique place in academia. The creative, embodied, collaborative activities typical to dance learning offer fresh insight to the literature on graduate attributes – both visible and invisible – all graduates from a given institution are expected to hold. Originality/value: A narrative methodology is employed to present a series of amalgam characters manifesting specific ways in which invisible graduate attributes inform pedagogies, student–teacher relationships and student understandings of their professional skills.